2008
DOI: 10.1590/s0103-507x2008000200003
|View full text |Cite
|
Sign up to set email alerts
|

Sepse na unidade de terapia intensiva: etiologias, fatores prognósticos e mortalidade

Abstract: SUMMARY BACKGROUND AND OBJECTIVES:Sepsis is the main cause of death in patients treated in intensive care units (ICU). The aim of this study was to evaluate etiology, prognostic factors and mortality of septic patients treated in ICU of Passo Fundo, Brazil. developed SIRS (58%). The most frequent cause of internation was neurological disease (28.9%), the most frequent site of infection was the respiratory tract (71.6%), and the most prevalent pathogens were gram-negative bacilli (53.2%). Mean APACHE II score w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
28

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 23 publications
3
23
1
28
Order By: Relevance
“…No que se refere aos diagnósticos de internação, resultado semelhante a este estudo foi encontrado em outra investigação 10 Interessante destacar que, na instituição investigada na presente pesquisa, já existe uma unidade de cardiologia intensiva, para onde são encaminhados pacientes com dano cardiovascular. Dessa forma, os dados encontrados são relativos à internação em UTI geral, excluindo-se as patologias cardíacas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…No que se refere aos diagnósticos de internação, resultado semelhante a este estudo foi encontrado em outra investigação 10 Interessante destacar que, na instituição investigada na presente pesquisa, já existe uma unidade de cardiologia intensiva, para onde são encaminhados pacientes com dano cardiovascular. Dessa forma, os dados encontrados são relativos à internação em UTI geral, excluindo-se as patologias cardíacas.…”
Section: Discussionunclassified
“…Em relação às infecções, em outros estudos 6,10 observaram-se taxas um pouco maiores de infecções com 53,4% e 53,8% respectivamente. Diferentemente do presente estudo, outra investigação realizada sobre o tema 6 , aponta que o sitio mais prevalente foi o urinário, com 43%; em segundo lugar apareceu a pneumonia associada à ventilação mecânica com 30% e a infecção da corrente sanguínea incidiu em 14% da população estudada.…”
Section: Discussionunclassified
“…Median APACHE II score for all patients was 21 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Non-survivor patients had a median APACHE II score that was signifi cantly higher (27; …”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in different regions confirm this distribution. 18,21,27,28 The literature suggests that there is a strong relationship between the time between organic dysfunction and the diagnosis of sepsis, as well as the time between antibiotic administration and mortality. 29 After the intervention, it was observed that providers in the emergency department made an earlier diagnosis of sepsis, with only 30 minutes from the time of dysfunction until the diagnosis; in the ICU, the time of administration of antibiotics reached approximately 12 minutes.…”
Section: Discussionmentioning
confidence: 99%